Non-Physical and Ambient Sexual Harassment of Women Undergraduate University Students in Canada: A Diary Study - Albert, Katelin (Violence against women, 2024)
Using a 60-day daily e-diary tool, 117 women undergraduate students reported sexual harassment on a Canadian university campus (4,283 diary surveys, collectively). Participants reported 181 incidents of both ambient sexual harassment (witnessing 40 incidents, hearing 106 unwelcomed sexual jokes/remarks) and targeted personal experiences of non-physical sexual harassment (35 incidents). Qualitative data document students’ descriptions of these encounters and contextualize how these are part of everyday student life. Findings show that students experience this harassment almost daily—in an ongoing, persistent, and normalized way—and that university can be a hostile environment where the possibility of daily unwanted sexual experiences is a lived, endemic reality.